Evolution and History of Chordophones in Asia: A Focused Study on Sāraṅgī - Lochan, Lochan (Bodhi: An Interdisciplinary Journal, 2024)
This paper explores the evolution and historical significance of chordophones in Asia, with a particular focus on the sāraṅgī and sarindā. Chordophones, defined as instruments that produce sound through vibrating strings, encompass a diverse range of stringed instruments. This study traces the roots of chordophones from ancient hunting bows to their complex modern forms, highlighting the similarities between sāraṅgī and sarinda, using the HornbostelSachs classification system. The sāraṅgī, renowned for its expressive capabilities, is deeply intertwined with the cultural practices of the Gandharva community in Nepal, while the sarindā, significant in the folk traditions of North and Eastern India and Pakistan, offers a contrasting yet complementary perspective on bowed instruments. This paper hence identifies shared characteristics and cultural contexts, emphasizing the intricate connections between theseinstruments and their roles in shaping regional identities, through comparative analysis. By examining the historical trajectories and contemporary significance of the sāraṅgī, this research contributes to a deeper understanding of the rich tradition of chordophones across Asia.